IMPROVING STUDENTS’ READING COMPREHENSION THROUGH LISTEN-READ-DISCUSS STRATEGY - Revi Permata Sari; Diah - Astriyanti; M. Iqbal Ripo Putra (IKIP PGRI Pontianak, 2023)
The a study conducted to find out how LRD works how the LRD strategy improves the student's reading comprehension of the spoken text. This study was conducted using a classroom behavioral survey. Conducted for her Grade 10 students at SMA Negeri 2 Sungai Raya for the academic year 2021/2022. The subject of this study was an IPA 3 science class, which consisted of 36 students. Field notes and reading comprehension tests served as means of data collection. To analyze the data, researchers used qualitative and quantitative data. For qualitative data, researchers used data reduction, data display, and inference to analyze the data. For quantitative data.Based on the result of qualitative data, the finding of this research showed that in the process of teaching and learning at Listen-Read-Discuss, the student’s behavior and activity in were classrooms were improved. The field note showed that the student’s performance improvement from the first round to the second round. Furthermore, quantitative data results showed that students get average marks of reading comprehension in the first cycle was 75,14 and in the second cycle was 80,14.Furthermore, the factor also influences improving students reading comprehension with the Listen-Read-Discuss strategy is an internal factor consisting of difficulties to understand main ideas, factual information, vocabulary, identifying references, and identifying inferences. Based on research results, in this case, the authors recommends to teachers that teachers should make better and more creative ways in applying techniques to teach reading skills. It can overcome students' difficulties in understanding longer reading materials and texts and improve students' understanding of the material being taught.Key words: Reading comprehension, listen-read-discuss, classroom action research in the classroom.